2016
DOI: 10.1039/c6tc01939k
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic π–π driven supergelation, aggregation induced emission and columnar self-assembly of star-shaped 1,2,4-oxadiazole derivatives

Abstract: Effect of the number of flexible peripheral tails on the self-assembly of star-shaped molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 110 publications
2
26
0
1
Order By: Relevance
“…Similarly m ‐substituted hexacatenars exhibited single absorption maximum centered at 268 nm, while the tetracatenar 2a exhibited an absorption maximum centered at 265 nm with a broad shoulder at 290 nm (Figure a, Table ). It should be noted that in the case of star shaped 1,2,4‐oxadiazole derivatives only single band was observed at 278 nm . m ‐substituted compounds exhibited blue shifted absorption maximum in comparison to p ‐substituted compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly m ‐substituted hexacatenars exhibited single absorption maximum centered at 268 nm, while the tetracatenar 2a exhibited an absorption maximum centered at 265 nm with a broad shoulder at 290 nm (Figure a, Table ). It should be noted that in the case of star shaped 1,2,4‐oxadiazole derivatives only single band was observed at 278 nm . m ‐substituted compounds exhibited blue shifted absorption maximum in comparison to p ‐substituted compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic Voltammograms showed that these molecules exhibit comparable HOMO, LUMO values irrespective of the position of the substitution to the central benzene ring (HOMO: −6.04 to −6.12 eV; LUMO: −2.21 to −2.31 eV). In comparison to the star shaped derivatives these molecules exhibit higher HOMO and lower LUMO levels (HOMO: −6.17 to −6.31 eV; LUMO: −1.96 to −2.09 eV) . Though the band gaps of these compounds are high (E g,opt =3.87‐3.89 eV), they were found to be lower than the band gaps of the corresponding star shaped molecules (E g,opt ≈ 4.22 eV) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1948, Schaefgen and Flory reported formation of mesophases of interesting mesomorphic and photophysical properties. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] The applications of starshaped molecules as building units for dendrimers 32,33 as well as in supramolecular host-guest chemistry have been also reported. 34,35 Moreover, the interesting biological activities of some diverse multivalent scaffolds adamantane have been recently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Такие материалы являются ключевыми при создании новых электронных и оптоэлектронных устройств. Так, соединения на основе 1,3,4-оксадиазола и тристриазолотриазинов находят широкое применение при разработке электронно-транспортных/дырочно-блокирующих материалов, которые служат светоизлучателями в электролюминесцентных диодах [7][8][9][10].…”
Section: Introductionunclassified